Donor-derived CD19 chimeric antigen receptor T cells. Issue 6 (November 2015) - Singh, Nathan; Barrett, David M.
Abstract : Purpose of review: As immunotherapy matures into possible front-line therapy, new approaches are necessary to expand the capacity to treat more patients. Although most technologies for chimeric antigen receptor (CAR) therapies require autologous T cells, 'off the shelf' sources are highly desired. Recent findings: Sources of T cells for modification with CARs include cord blood and either related or unrelated allogeneic donors. Strategies to manipulate these sources focus on reducing the risk of alloreactivity, while maintaining the potential for high function and long persistence associated with successful CAR T-cell therapies. Summary: Recent research implies that manipulating nonautologous T-cell sources can result in well tolerated and effective products, but work remains to determine if these approaches will reach the efficacy of autologous products.